EFFORTS TO INCREASE FAMILY INCOME INDEPENDENTLY THROUGH HOME AGRICULTURAL ECONOMY: CONTRIBUTION OF PINE TAPPING (PINUS MERKUSII) - Irada Sinta; Fadli; Rico Nur Ilham; Muhammad Multazam (RADJA PUBLIKA, 2025)
Pine resin (Pinus merkusii) is one of the non-timber forest products (NTFPs) that plays an important role in increasing the income of rural communities. This study aims to analyze the level of income and contribution of pine resin tapping to family income in Cane Toa Village, Rikit Gaib District, Gayo Lues Regency. The method used was a census of 55 pine resin tapper respondents. Data were analyzed quantitatively using the contribution formula and household income analysis. The results showed that the average income from pine resin tapping was IDR 3,319,818.4 per production, while income from other sectors reached IDR 4,156,370.85. The total average income of tapper families was IDR 7,476,189.31 per production. The contribution of pine resin tapping to total family income was recorded at 44.4%, included in the